A Program Based on Productive Habits of Mind in Social Studies to Develop Analytical Thinking Skills Among Middle School Students (Global Scientific Review, 2024)
The study aims to determine the program's effectiveness based on productive habits of mind to develop analytical thinking skills among middle school students in the General Directorate of Education of Diyala Governorate. The researchers chose the women’s secondary schools and Al-Mohsen secondary schools. The researchers used the experimental method to research it from two groups, control and experimental, and the research sample consisted of 60 students. The second grade is intermediate, and several behavioral objectives were formulated, numbering (30). The researchers also formulated a test for his research tool, which was represented by testing analytical thinking skills. The research showed that the experimental group outperformed the control group in analytical thinking skills. The researchers concluded that teaching is according to the program based on productive habits of mind. Among the students, it helped develop the students’ mental and thinking skills, which helped increase the orientation towards learning social studies and the suitability of the productive habits of mind strategy to the level of middle school students, which helped develop the students’ thinking skills. The researchers recommended the necessity and importance of working on developing social studies curricula. In the various educational stages to achieve growth and development in students’ thinking, especially analytical thinking abilities, according to the nature and characteristics of the students